Competency-based, multicomponent teaching reform in medical imaging technology: a quasi-experimental study - Qi, Chunhua; Zhou, Shuli (Frontiers in Medicine, 2026)
IntroductionThe growing demand for medical technology highlights the need to improve education in medical imaging technology (MIT). Traditional teaching presents concrete challenges, such as lecture-centric instruction, limited simulation time, and weak school–hospital coordination, which have prompted curricular reform. This study evaluated a competency-based, multicomponent teaching reform that integrated staged training, digital and simulation resources, updated methods, and school–enterprise collaboration.Materials and methodsWe conducted a quasi-experimental, sequential-cohort study comprising a control cohort that received routine teaching (July 2021–June 2022; n = 60) and a subsequent intervention cohort that received the reformed program (July 2022–July 2023; n = 60). The primary outcomes were theoretical knowledge (0–100 written exams) and hands-on imaging skills, assessed using an OSCE-style, station-based practical exam (0–100). The secondary outcomes included learning ability, clinical reasoning/analysis, and problem-solving, which were measured using Likert-scale instruments aggregated to a 0–100 scale, as well as participation in competitions and research, publication rates, professional examination pass rates, employment, and satisfaction. Statistical comparisons were performed using independent samples t-tests and χ2/Fisher’s tests, with a two-sided α = 0.05.ResultsThe intervention cohort demonstrated significant improvements in theoretical knowledge (91.1 ± 6.5 vs. 86.5 ± 5.8; mean diff +4.7; p < 0.001) and practical skills (92.1 ± 5.4 vs. 82.4 ± 6.1; +9.7; p < 0.001), as well as higher scores for learning (+11.4), reasoning/analysis (+12.0), and problem-solving (+11.5) (all p < 0.001). Co-curricular and career outcomes also favored the intervention cohort: research participation (50.0% vs. 20.0%), publications (23.3% vs. 3.3%), professional examination pass rates (100% vs. 90%), employment (100% vs. 86.7%), and satisfaction (98.3% vs. 86.7%). However, because the cohorts were not randomized and were drawn from a single center, between-cohort differences may partly reflect selection or cohort effects.ConclusionMulticomponent teaching reform was associated with higher knowledge and skills scores and improved co-curricular indicators. Given the non-randomized, single-center, sequential-cohort design, these findings are associative, subject to selection bias, and have limited generalizability. Multisite studies using validated measures are needed to estimate causal impact.